2020
DOI: 10.1002/jhrm.21412
|View full text |Cite
|
Sign up to set email alerts
|

A description of medical malpractice claims involving advanced practice providers

Abstract: This article is ASHRM CE eligible. Earn 1.0 credit hours of Continuing Education by passing an online quiz based on your reading at ASHRM.org/JournalCE. [This article is updated on November 10, 2020, after first online publication, to identify it as a CE article.] Background: The number of physician assistants (PAs) and advanced practice registered nurses (APRNs), together known as advanced practice providers (APPs), has risen dramatically. The goal is identifying characteristics of paid medical malpractice cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Recently published data using the Candello database from all medical specialties found that the highest median indemnity paid was among PA claims ($353,000; interquartile range [IQR] $98,725–$1,327,975) compared with no‐extender claims ($192,334, IQR $55,065–$489,039) and NP claims ($57,674; IQR $15,417–$619,626) 11 . This significantly higher indemnity paid on PA claims relative to NP claims is inconsistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently published data using the Candello database from all medical specialties found that the highest median indemnity paid was among PA claims ($353,000; interquartile range [IQR] $98,725–$1,327,975) compared with no‐extender claims ($192,334, IQR $55,065–$489,039) and NP claims ($57,674; IQR $15,417–$619,626) 11 . This significantly higher indemnity paid on PA claims relative to NP claims is inconsistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about medicolegal and cost risks of emergency practice with APPs despite their increasing presence on multidisciplinary ED care teams 10,11 . Characterizing the malpractice cases among these practitioner types has important implications for workforce development, ED staffing, patient safety, and risk mitigation for supervisory physicians.…”
Section: Introductionmentioning
confidence: 99%
“…This outcome was selected as it was deemed by the authors relevant to motivating practice change and had face validity as a marker of malpractice environment, as well as consistency with methods used in other studies of malpractice environment. 11,[22][23][24] We chose variables a priori to include in the model. For claimant age, the odds ratio is per year.…”
Section: Discussionmentioning
confidence: 99%
“…The outcome used in the regression analysis (Tables 2 and 3) was a case closing with an indemnity payment. This outcome was selected as it was deemed by the authors relevant to motivating practice change and had face validity as a marker of malpractice environment, as well as consistency with methods used in other studies of malpractice environment 11,22–24 …”
Section: Methodsmentioning
confidence: 99%
“…Physicians are held legally responsible for the acts of their physician extenders and in most cases are sued along with them on the premise that it is the responsibility of the physician to train and supervise physician extenders. [31][32][33] The three legal theories commonly attributing to physician liability are vicarious liability, negligent supervision, and hiring. 31 It is imperative to enhance safe patient care by having systems in place for working with PAs or NPs.…”
Section: Discussionmentioning
confidence: 99%